An Online Electric Power Quality Disturbance Detection System - Yildirim, Ozal; Eristi, Belkis; Eristi, Huseyin; Unal, Sencer; Erol, Yavuz; Demir, Yakup (Ieee, 2016)
In this study, an FPGA based online monitoring system was developed for detection of power quality disturbances. The developed system has the capability to instantly detect commonly seen PQ disturbances such as voltage sag, voltage swell and interruption occurring on real-time three-phase voltage signals obtained from the electric power system. The data of the detected disturbance events are transferred to the visual software prepared in the computer environment by means of the UDP/IP communication module embedded in the FPGA. This PQ disturbance detection system was tested upon installation at three different measuring points across the campus of Tunceli University. It was seen from the test results examined that the detection system successfully identified the PQ disturbance events.
51st International Universities Power Engineering Conference (UPEC) -- SEP 06-09, 2016 -- Coimbra Inst Engn, Coimbra, PORTUGAL
Keywords: Power quality; PQ disturbance; FPGA